The role of seasonality of mineral dust concentration and size on glacial/interglacial dust changes in the EPICA Dronning Maud Land ice core. Issue 19 (5th October 2015) - Wegner, Anna; Fischer, Hubertus; Delmonte, Barbara; Petit, Jean‐Robert; Erhardt, Tobias; Ruth, Urs; Svensson, Anders; Vinther, Bo; Miller, Heinrich
Abstract We present a record of particulate dust concentration and size distribution in subannual resolution measured on the European Project for Ice Coring in Antarctica (EPICA) Dronning Maud Land (EDML) ice core drilled in the Atlantic sector of the East Antarctic plateau. The record reaches from present day back to the penultimate glacial until 145, 000 years B.P. with subannual resolution from 60, 000 years B.P. to the present. Mean dust concentrations are a factor of 46 higher during the glacial (~850–4600 ng/mL) compared to the Holocene (~16–112 ng/mL) with slightly smaller dust particles during the glacial compared to the Holocene and with an absolute minimum in the dust size at 16, 000 years B.P. The changes in dust concentration are mainly attributed to changes in source conditions in southern South America. An increase in the modal value of the dust size suggests that at 16, 000 years B.P. a major change in atmospheric circulation apparently allowed more direct transport of dust particles to the EDML drill site. We find a clear in‐phase relation of the seasonal variation in dust mass concentration and dust size during the glacial (r(conc, size) = 0.8) but no clear phase relationship during the Holocene (0 < r(conc, size) < 0.4). With a simple conceptual 1‐D model describing the transport of the dust to the ice sheet using the size as an indicator for transport intensity, we find that the effect of the changes in the seasonality of the source emission strength and the transport intensity on the dust decrease over Transition 1 can significantly contribute to the large decrease of dust concentration from the glacial to the Holocene.